Genetic evaluation of hulless barley (Hordeum vulgare) genotypes for morpho-physiological traits and stripe rust resistance - SINGH, JOGENDRA; KUMAR, SUDHEER; GANGWAR, O P; KUMAR, DINESH; KUMAR, LOKENDRA; LAL, CHUNI; VERMA, AJAY; MALIK, REKHA; KHARUB, A S; VERMA, R P S; SINGH, G P (The Indian Journal of Agricultural Sciences, 2024)
Nowadays, hulless barley (Hordeum vulgare L.) is gaining importance as a raw material for food industry due to its highly nutritive value. Non-availability of high yield and disease resistant varieties has restricted its production in marginal areas over the last two decades. Therefore, an experiment was conducted during 2017–18 and 2018–19 at the Seed and Research Farm of ICAR-Indian Institute of Wheat and Barley Research, Karnal, Haryana to characterized 11 exotic hulless barley genotypes and 4 Indian barley cultivars for morpho-physiological characters and stripe rust resistance. Seedling resistant test for stripe rust was done at Regional Station (ICAR-Indian Institute of Wheat and Barley Research), Flowerdale, Shimla, Himachal Pradesh. Highly significant genotypic differences were found for morpho-physiological traits during analysis of variance. Genotype DWRNB28 showed a good combination of desirable traits, viz. early maturity (118 days), dwarf plant height (64.4 cm) and high 1000-grain weight (55.2 g). Maximum number of tillers per meter (149) was observed in DWRNB17. Genotype DWRNB25 was found resistant to maximum pathotypes (6S0, 7S0, and Q) at the seedling stage. DWRNB23 and DWRNB25 with pooled ACI=0 and ACI=0.04 respectively, were found immune to stripe rust in field conditions. These promising genotypes can be utilized as donor parents for the development of high-yielding and stripe-rust-resistant hulless barley varieties.